2022
DOI: 10.4048/jbc.2022.25.e31
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognosis of Estrogen Receptor Low-Positive Breast Cancer

Abstract: Purpose The updated American Society of Clinical Oncology/College of American Pathologists guideline for estrogen receptor (ER) testing recommends that breast cancer with ER expression in 1–10% of tumor cells should be reported as ER-low positive (ER low ), although limited data are available on the overall benefits of endocrine therapy. We investigated the clinicopathological characteristics and clinical outcomes of ER low breast cancer and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Prior studies that predominantly included patients with invasive ductal carcinoma have shown associations between ER low status and worse DFS; our findings might differ because we used a different threshold for “ER low,” versus a differential impact of ER expression on ILC than IDC. While relatively lower ER positivity was associated with different clinicopathologic features in our study, it did not seem to drive outcomes, while PR low versus high status was an important predictor of DFS in this study [ 14 ].…”
Section: Discussionmentioning
confidence: 69%
“…Prior studies that predominantly included patients with invasive ductal carcinoma have shown associations between ER low status and worse DFS; our findings might differ because we used a different threshold for “ER low,” versus a differential impact of ER expression on ILC than IDC. While relatively lower ER positivity was associated with different clinicopathologic features in our study, it did not seem to drive outcomes, while PR low versus high status was an important predictor of DFS in this study [ 14 ].…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, patients classified as ER-low were not included in our study. Approximately 2 − 3% of breast cancers have been reported to be ER-low and there is limited data on the overall benefit of endocrine therapy in these patients [ 34 ]. Consequently, we suspect the exclusion of this patient subgroup from our study may have influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the clinical characteristics and prognosis of low ER-positive patients and found that low ER-positive breast cancers behave like HR-negative tumors [ 12 , 13 , 14 ]. Several studies have recently revealed the importance of subdividing HR-positive as single hormone-positive receptors or low PR patients [ 11 , 15 , 16 ]. Phenotypes of a single HR can determine differences in patient demographics, tumor characteristics, and prognostic outcomes, such as unfavorable characteristics and poorer survival than ER-positive/PR-positive subtypes [ 11 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%